Regulatory mechanism of Haa1p and Hap4p in Saccharomyces cerevisiae to mixed acetic acid and formic acid when fermenting mixed glucose and xylose - Xin-Yu Xiao; Bo Li; Zi-Yuan Xia; Quan Zhang; Cai-Yun Xie; Yue-Qin Tang (Microbial Cell Factories)
Abstract Background Acetic and formic acid are two common inhibitors that coexist with glucose and xylose in lignocellulosic hydrolysates, which impair the fermentation performance of Saccharomyces cerevisiae. Enhancing yeast tolerance to these inhibitors is crucial for efficient industrial bioethanol production. Previous transcriptomic studies have indicated the involvement of the transcription factors Haa1p and Hap4p in the cellular response to mixed acetic and formic acid stress. This study aimed to further elucidate their regulatory roles in conferring tolerance to this combined stress condition. Comparative transcriptomic analysis was conducted using the engineered strains s6H3 (HAA1-overexpressing) and s6P5 (HAP4-overexpressing), in comparison with the original strain s6. Results Both HAA1 and HAP4 overexpression improved fermentation performance, both in the presence and absence of inhibitors. HAA1 overexpression led to a greater number of differentially expressed genes (DEGs) under mixed acid stress compared to non-inhibitory conditions. Genes involved in glycolysis, the pentose phosphate pathway (PPP), necroptosis, and ribosome biogenesis were significantly downregulated, whereas those associated with the glyoxylate cycle, nucleotide metabolism, and RNA polymerase activity were significantly upregulated. In contrast, HAP4 overexpression resulted in fewer DEGs under acid stress conditions, which may be attributed to the intrinsic induction of HAP4 in the original strain s6 under acid exposure. Under these conditions, genes related to metabolic regulation, RNA processing, and transcription were significantly downregulated, while those involved in transport, ribosome biogenesis, genome stability, and sporulation were significantly upregulated. Collectively, both Haa1p and Hap4p appear to regulate other transcription factors, thereby indirectly influencing global gene expression in response to mixed acetic and formic acid stress. Conclusions This study provides the experimental evidence for the protective role of Haa1p and Hap4p under combined acetic and formic acid stress. Regulatory mechanisms underlying the responses of Haa1p and Hap4p to combined acid stress were identified, expanding current understanding of yeast stress adaptation.